Modelling dynamic loadings of a tidal stream turbine in combined wave-current-turbulence environment. (March 2022) - Li, Qian; Venugopal, Vengatesan; Barltrop, Nigel
Abstract: The understanding of hydrodynamic loadings on a Tidal Stream Turbine (TST) is important to its design, deployment and operation. An assessment involving combined wave-current-turbulence effects is essential for the prediction of the loadings and turbine performance. TSTs are often located in regions of localized high current, so the incident waves will be modified as they travel onto that higher current. This paper proposes a methodology which is capable of generating the combined wave-current effects with the integration of a model of the incident turbulence. The algorithm and methodology presented in this paper are implemented in the OpenFAST software. The modified numerical model has been validated by comparing its outputs to the scale model tests conducted in Edinburgh University's FloWave wave-current facility. The impact of combined waves, currents, and turbulence intensity on power production of a TST has been quantitatively investigated. The results show that the wave-current interaction effects are significant, in particular when waves travel in opposite direction to currents; in which case the loads were underestimated by 40.3% in comparison to excluding the wave-current interaction effects. Furthermore, the ambient turbulent flow is observed to affect the loadings and the performance of the TST, and the output suggests a discrepancy around 45.6% between different turbulence intensity levels.